Numerical Simulation on Shear Behavior of Double Rough Parallel Joints Under Constant Normal Stiffness Boundary Condition - Liu, Jie; Wu, Jiahong; Li, Xiaoshuang; Zhang, He; Song, Yanbin (Frontiers in Earth Science, 2022)
The shear characteristics of rock joints under constant normal stiffness (CNS) boundary condition are critical to the stability of underground engineering rock mass. Five different rock joint profiles with random morphology were constructed by using independent segmentation method of Hurst index. Based on the continuously yielding (CY) joint model, the discrete element calculation model of double rough parallel joints with different joint surface roughness and spacing of joints under CNS boundary condition was established by using UDEC software to investigate the shear effect of joints under CNS boundary condition. The results show that under CNS boundary condition, the shear stress, normal displacement, normal stress and surface resistance index (SRI) all increase with the increase of joint surface roughness coefficient (JRC) for both single- and double-joint specimens, and these of the single-joint are greater than these of the double-joint. With the increase of the joint spacing d, the peak shear stress τy and the peak surface resistance index (SRIp) show a gradually increasing trend, and the influence of d on τy and SRIp is greater with the increase of JRC, and both τy and SRIp show a linear increasing trend with the increase of JRC. With the increase of d for the same JRC, both normal displacement and normal stress show a gradually increasing trend and also the increase amplitudes gradually increase; with the increase of JRC for the same d, the two parameters also show an increasing trend.